PERSONAL BRANDING USTAD HANAN ATTAKI DI MEDIA SOSIAL - TEGUH NURJAMAN; RITA HERLINA (UNIVED PRESS, Universitas Dehasen Bengkulu, 2021)
Each of the preachers has their own characteristics in the delivery of their da'wah messages. In this study, the personal ustad Hanan Attaki has a very unique and different style. This is the background of this research with the theme of Ustad Hanan Attakidi's personal branding on social media. This study aims to determine the method of preaching Ustad Han Attaki on social media in forming personal branding and to find out the approach style of Ustad Han Attaki to the congregation in typing personal branding. The methodology used in this research is a qualitative method with a case study approach. Data collection techniques used were observation, direct interviews, and document analysis. The results of this study indicate that Ustad Hanan Attaki's personal branding shows how to preach on social media using persuasive communication through light studies and prioritizing issues around the lives of young people, and using a persuasive language style that is gentle and contemporary, and has a style of appearance. on social media which is more executive, calm, hits, and easy to recognize, has become the hallmark of the preaching of Ustadh Hanan Attaki on social media.